(untitled) (World Bulletin of Public Health, 2024)
In modern conditions, health care of military personnel plays a key role in ensuring national security. In this context, medical examination becomes an important tool for maintaining a high level of physical and mental health of servicemen. The article will consider the justification of indicators for assessing the effectiveness of medical examination of servicepersons of the Republic of Uzbekistan